The Influence Of Independence, Integrity On Fraud Detection In Jakarta Public Accounting Firm - Raselly Eunike Hasibuan; Hisar Pangaribuan (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this research is to ascertain the impact of auditor independence and integrity on fraud detection in Jakartan public accounting firms. This research sample data collection uses the saturated sample method. The data was collected by distributing questionnaires to public accounting firms in Jakarta, and there were 10 public accounting firms that received researcher questionnaires, of these 10 offices only 33 auditors were willing to fill out the questionnaires distributed to auditors. SPSS version 22 is used in this study to analyze the data In this study, auditor independence (X1) and integrity (X2) are the independent variables, and fraud detection (Y) is the dependent variable. The t test results show that the significant level of auditor integrity is 0.000 <0.05 and auditor independence is 0.526>0.05. The study's findings show that while auditor independence has no bearing on fraud detection in Jakarta's public accounting firms, integrity has a favorable effect on the detection of auditor fraud in that city.